The production of yeast cell wall using an agroindustrial waste influences the wall thickness and is implicated on the aflatoxin B1 adsorption process - Pereyra, Carina Maricel (2018)
The objectives of this study were: to evaluate the use of dry distillery grain soluble extract - DDGse to produce yeast biomass and to obtain cell wall (CW), to use the CW as an aflatoxin B1 (AFB1) adsorbent, to study the variation in the composition and thickness of the CW under the influence of DDGse to evaluate their implication on the adsorption process using transmission electron microscopy (TEM) and fourier-transform infrared spectroscopy (FITR). The production of biomass and CW were variable. The CW thickness values showed that S. boulardii strain grown in yeast extract peptone dextrose (YPD) or DDGse medium, with no significant differences observed. The thickness of the CW for S. cerevisiae (RC012 and VM014) were increased when the cells were grown in DDGse medium, the thickness was almost double compared to the values obtained in YPD medium. The spectra IR of each CW in the two culture media shown regions corresponding to polysaccharides, proteins and lipids. Cells grown in DDGse medium adsorbed more AFB1 than those grown in YPD. The CW adsorbed more AFB1 than the same amount of whole cell. Future studies should be done to determine the type of carbohydrates and the relationship between chitin - beta glucans responsible for mycotoxin adsorption.